PENGARUH PENGALAMAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. BANK BNI TBK CABANG PAMEKASAN YANG DIMEDIASI OLEH PROFESIONALISME - Mohammad Khotib; Chamariyah Chamariyah; Subijanto Subijanto (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2022)
The purposes of this study are: 1) To describe the work experience, compensation, professionalism and performance of employees of PT. Bank BNI Tbk Pamekasan Branch; 2) To test and analyze the effect of work experience on the performance of employees of PT. Bank BNI Tbk Pamekasan Branch; 3) To test and analyze the effect of work experience on professionalism at PT. Bank BNI Tbk Pamekasan Branch; 4) To test and analyze the effect of compensation on professionalism at PT. Bank BNI Tbk Pamekasan Branch; 5) To test and analyze the effect of compensation on the performance of employees of PT. Bank BNI Tbk Pamekasan Branch; 6) To test and analyze the effect of professionalism on the performance of employees of PT. Bank BNI Tbk Pamekasan Branch; 7) To test and analyze the effect of work experience on the performance of employees of PT. Bank BNI Tbk Pamekasan Branch mediated by professionalism; and 8) To test and analyze the effect of compensation on the performance of employees of PT. Bank BNI Tbk Pamekasan Branch mediated by professionalism. This type of research is explanatory, the research approach uses a quantitative approach, the number of samples is 96 employees. The sampling method used total sampling. Data analysis using SEM-PLS. Based on data analysis using PLS, the results showed that; 1) Work experience has a significant effect on employee performance, with the original sample value of 0.288; 2) Work experience has a significant effect on professionalism, with the original sample value of 0.388; 3) Compensation has a significant effect on professionalism, with the original sample value of 0.513; 4) Compensation has a significant effect on employee performance, with the original sample value of 0.242; 5) Professionalism has a significant effect on employee performance, with the original sample value of 0.442; 6) Work experience has a significant effect on employee performance mediated by professionalism, with the original sample value of 0.171; 7) Compensation has no significant effect on employee performance mediated by professionalism, with the original sample value of 0.227. The significance value of all research variables at = 0.05 with a 95% confidence level. The variable that has a significant dominant effect is compensation for professionalism.